Mounting Pressures on the Rule of Law (Taylor & Francis, 2025)
This important book offers an original perspective on the rule of law, development, and democracy in Latin America, establishing a new approach in recognizing the realities of political economy as opposed to merely structural and institutional factors. With contributions from an international team of experts, the book outlines the main challenges that have arisen in the pursuit of a developmental agenda in the region, including subnational variations, state capture by local elites, variations in state capacity, border divergence from centrally designed perspectives, environmental conflicts, uneven access to justice and the role of international organizations. In doing so, the book explores the democratic and developmental implications of conflicts over the rule of law and its application, uneven enforcement, and state capture. Whether a reference tool for the seasoned scholar, a guide aiding practitioner's individual expertise or an introduction to students interested in the complex intersections between the rule of law, development and democracy, this book is a must-have for any library.